2010
DOI: 10.1007/s10530-010-9728-5
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of recruitment in two endemic palms on Lord Howe Island by invasive rats

Abstract: Invasive species may have negative impacts on many narrow range endemics and species restricted to oceanic islands. Predicting recent impacts of invasive species on long-lived trees is difficult because the presence of adult plants may mask population changes. We examined the impact of introduced black rats (Rattus rattus) on two palm species restricted to cloud forests and endemic to Lord Howe Island, a small oceanic island in the southern Pacific. We combined estimates of the standing size distribution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 41 publications
1
48
1
Order By: Relevance
“…Shiels and Drake (2011) found that the three largest seeds (17.9 -30.3 mm longest axial length) monitored in the field were among the most unattractive to R. rattus, whereas intermediate-sized seeds (5.2 -17.7 mm) suffered the highest level of predation (>50%), and the smallest seeds (0.5 -1.2 mm) were ingested but not destroyed. On Lord Howe Island, Auld et al (2010) found that R. rattus removed 94% of Lepidorrhachis mooreana palm fruit from trees, but a sympatric palm (Hedyscepe canterburyana) that has fruits 18 times larger in dry mass suffered much less (54%) removal by R. rattus. Pender et al (2013) showed that trapping R. rattus in a Hawaiian forest resulted in the reduction of fruit consumption and seed predation from 46% to just 4% for the endangered tree Cyanea superba.…”
Section: Impact On Plant Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Shiels and Drake (2011) found that the three largest seeds (17.9 -30.3 mm longest axial length) monitored in the field were among the most unattractive to R. rattus, whereas intermediate-sized seeds (5.2 -17.7 mm) suffered the highest level of predation (>50%), and the smallest seeds (0.5 -1.2 mm) were ingested but not destroyed. On Lord Howe Island, Auld et al (2010) found that R. rattus removed 94% of Lepidorrhachis mooreana palm fruit from trees, but a sympatric palm (Hedyscepe canterburyana) that has fruits 18 times larger in dry mass suffered much less (54%) removal by R. rattus. Pender et al (2013) showed that trapping R. rattus in a Hawaiian forest resulted in the reduction of fruit consumption and seed predation from 46% to just 4% for the endangered tree Cyanea superba.…”
Section: Impact On Plant Communitiesmentioning
confidence: 99%
“…Some responses to R. rattus impacts may mask others, particularly over extended periods, which makes the species composition of the community potentially important for assess-ing rat impacts. For these reasons, assessments of plant community change as a result of R. rattus are generally restricted to their effects on seeds and seedlings (Shaw et al 2005, Abe 2007, Wegmann 2009, Auld et al 2010, Shiels and Drake 2011.…”
Section: Impact On Plant Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Four rodents (black rats, Rattus rattus; Norway rats, Rattus norvegicus; Pacific rats, Rattus exulans, and house mice, Mus musculus) are widespread invasive species that have been shown to negatively impact insular floras (Cuddihy and Stone 1990;Campbell and Atkinson 1999;Campbell and Atkinson 2002;Towns et al 2006;Angel et al 2009;Meyer and Butaud 2009;Auld et al 2010). These rodents may have indirect impacts upon plants by modifying plant habitat and ecosystem functioning.…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, for example, ground disturbance by wild pigs (Sus scrofa) can have a detrimental impact on plant establishment, plant growth and ecosystem structure, and can expedite invasion by weeds (Krull et al 2016). Rodents such as rats and mice can limit plant establishment by consuming seed (Auld et al 2010;McConkey et al 2003), and browsing by herbivores such as red deer (Cervus elaphus scoticus) can alter plant growth and cause loss of seedlings (Forsyth et al 2015). In Australia, six species of deer have established feral populations and the environmental degradation they cause through herbivory, trampling and weed dispersal has been listed as a 'key threatening process' potentially impacting rainforest plants and communities (http:// www.environment.nsw.gov.au/determinations/FeralDeerKtp.htm, accessed 27 November 2017).…”
Section: Threats and Lossesmentioning
confidence: 99%